Review of advanced energy devices for the minimal access gynaecologist. (27th September 2021) - Bentham, Gemma L; Preshaw, Jessica
Abstract : Key content: Contemporary energy devices utilise advanced bipolar, ultrasound, hybrid technology, plasma beam and laser energy. Each energy modality has specific characteristics influencing its particular benefits and disadvantages. Gynaecologists must be aware of the available energy modalities to select the optimum device. Minimal access surgeons must demonstrate a comprehensive understanding of their instruments to ensure surgical success and safety. Learning objectives: To understand the biophysics of advanced energy devices and their practical applications. To review advantages, disadvantages and safety issues associated with each modality and offer practical tips and problem‐solving for commonly available devices. To enable surgeons to select the optimal device for their surgical tasks. Ethical issues: Trainee minimal access surgeons should have solid theoretical knowledge of energy devices before performing hands‐on surgery. Consideration of the safety aspects of energy devices will enable surgeons to minimise harm to their patients. Potentially high investment costs necessitate consideration of the anticipated benefits of energy devices to ensure value for money.